What Drives Booms and Busts in Value? - Campbell, John Y.,Giglio, Stefano,Polk, Christopher (National Bureau of Economic Research, 2023)
Value investing delivers volatile returns, with large drawdowns during both market booms and busts. This paper interprets these returns through an intertemporal CAPM, which predicts that aggregate cash flow, discount rate, and volatility news all move value returns. We document that indeed these shocks explain a large fraction of quarterly value returns over the last 60 years. We also distinguish between the intra-industry and inter-industry components of value, showing that the ICAPM explains the former better. Finally, we develop a novel methodology to perform this decomposition at the daily frequency, using it to interpret value returns during the Covid-19 pandemic
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Kapitalanlage; Anlageverhalten; CAPM; value investing; Asset Pricing; Trading Volume; Bond Interest Rates